Development of an Amperometric Hydrogen Peroxide Biosensor based on the Immobilization of Horseradish Peroxidase onto Nickel Ferrite Nanoparticle-Chitosan Composite - Yalçıner, Furkan; Çevik, Emre; Şenel, Mehmet; Baykal, Abdülhadi (Nano-Micro Letters, 2011)
Nickel ferrite (NiFe2O4) nanoparticles have been dispersed in chitosan solution in order to fabricate nanocomposite films. Horseradish peroxidase (HRP) has been immobilized onto this chitosan-NiFe2O4 nanocomposite film via physical adsorption. The size of the NiFe2O4 nanoparticles has been estimated using X-ray diffraction pattern and scanning electron microscopy (SEM) to be 40±9 nm. The chitosan-NiFe2O4 nanocomposite film and HRP/chitosan-NiFe2O4 bioelectrode have been characterized using SEM technique. The HRP/chitosan-NiFe2O4 nanocomposite bioelectrode has a response time of 4 s, linearity as 0.3 to 12mM of H2O2, sensitivity as 22 nA/mM. The effects of pH and the temperature of the immobilized HRP electrode have also been studied.